Krievijas-Ukrainas kara naratīvi “Channel One Russia”, “Current Time” un “TV Rain” vakara ziņu raidījumos, un to dienaskārtība - Zonnenberga-Zamberga, Beāte Kristiāna (Latvijas Universitāte, 2023)
Bakalaura darba „Krievijas-Ukrainas kara naratīvi “Channel One Russia”, “Current Time” un “TV Rain” vakara ziņu raidījumos, un to dienaskārtība” mērķis ir noskaidrot visu trīs iepriekš minēto mediju dienaskārtības, ņemot vērā kanālos pausto ziņu naratīvu. Pētījuma problēma ir šķietami pretstati naratīvos Krievijas-Ukrainas kara notikumu atspoguļošanā trīs krievvalodīgajos medijos. Pētījuma mērķis ir veikt trīs krievvalodīgo mediju vakara ziņu pārraižu dienaskārtības analīzi un attiecīgi naratīvu noteikšanu. Lai sasniegtu mērķi tika gūts teorētiskais pamats, balstoties uz M. Makkomba, D. Šova, Entmana, J. V. Dīringa teorijām. Pētījuma metodoloģijā izmantota kvantitatīvā kontentanalīze, kā arī Aļģirda Ž. Greimasa aktantu modelis, pēc kura veikta ziņu naratīvu analīze. Rezultātos noskaidrots, ka “Channel One” pauž dezinformāciju, tendenciozi atainojot Krievijas Federāciju kā galveno virzītājspēku, kamēr “Current Time” un “TV Rain” objektīvi atspoguļo aktualitātes Krievijā, Ukrainā, un citas ārpolitikas norises, kuras ietekmē Krievijas kara notikumus Ukrainā, un otrādi.

The aim of the bachelor thesis " Russia-Ukraine war reporting narratives in “Channel one Russia”, “Current Time” and “TV Rain” evening program agendas" is to clarify the agendas of all three above-mentioned media, taking into account the news narrative expressed in the channels. The research problem is the apparent contrasts in the narrative coverage of the events of the Russian-Ukrainian war in the three Russian-language media. The purpose of the study is to analyze the agenda of three Russian-language evening news broadcasts and, accordingly, determine the narratives they are providing. In order to achieve the goal, the theoretical basis was obtained, based on the theories of M. McComb, D. Shaw, Entman, J.V. Dearing. Quantitative content analysis is used in the research methodology, as well as Alģirda Ž. Greimas' actant model, according to which the analysis of news narratives was carried out. The results revealed that "Channel One" conveys disinformation, tendentially portraying the Russian Federation as the main driving force, while "Current Time" and "TV Rain" objectively reflect current events in Russia, Ukraine, and other foreign policy developments that affect the Russian war in Ukraine, and vice versa. In order to achieve the goal, the theoretical basis was obtained, based on the theories of M. McComb, D. Shaw, Entman, J.V. Dearing. Quantitative content analysis is used in the research methodology, as well as Alģirda Ž. Greimas' actant model, according to which the analysis of news narratives was carried out. The results revealed that "Channel One" conveys disinformation, tendentially portraying the Russian Federation as the main driving force, while "Current Time" and "TV Rain" objectively reflect current events in Russia, Ukraine, and other foreign policy developments that affect the Russian war in Ukraine, and vice versa.
Russia-Ukraine war reporting narratives in “Channel one Russia”, “Current Time” and “TV Rain” evening program agendas
Keywords: Komunikācijas zinātne; dienaskārtība; naratīvs; Ukraina; karš; pārraide